2014
DOI: 10.4103/0973-6247.126693
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype frequencies of blood group systems (Rh, Kell, Kidd, Duffy, MNS, P, Lewis, and Lutheran) in blood donors of south Gujarat, India

Abstract: Background:This is the first study on phenotype frequencies of various blood group systems in blood donors of south Gujarat, India using conventional tube technique.Material and Methods:A total of 115 “O” blood group donors from three different blood banks of south Gujarat were typed for D, C, c, E, e, K, Jka, Lea, Leb, P1, M, and N antigens using monoclonal antisera and k, Kpa, Kpb, Fya,Fyb, Jkb, S,s, Lua, and Lub antigens were typed using polyclonal antisera employing Indirect Antiglobulin Test. Antigens and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 7 publications
(11 reference statements)
10
29
2
Order By: Relevance
“…10 The antigen frequencies of major blood group systems have been widely reported in the Caucasian, African, Indian, and Chinese populations. [11][12][13][14] However, information on antigen frequencies in Saudi Arabia has been limited to the ABO and Rh blood group systems. [3][4][5]7 To the best of our knowledge, this is the first study to report the extended antigen phenotyping of the major blood group systems in Saudi Arabia, specifically in the Eastern region.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…10 The antigen frequencies of major blood group systems have been widely reported in the Caucasian, African, Indian, and Chinese populations. [11][12][13][14] However, information on antigen frequencies in Saudi Arabia has been limited to the ABO and Rh blood group systems. [3][4][5]7 To the best of our knowledge, this is the first study to report the extended antigen phenotyping of the major blood group systems in Saudi Arabia, specifically in the Eastern region.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The frequencies of c and e antigens in our study are high (99, 85%) ( Table 1 ) while the frequencies of C and E antigens are lower, respectively, 21.97% and 13.82%. Among whites, European, and Asian people, e antigen is the most popular, and then comes C antigen [ 17 ]. As regards to C and E antigens, frequencies are higher than in our study (C 70% and E 26%) [ 5 , 9 , 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among whites, European, and Asian people, e antigen is the most popular, and then comes C antigen [ 17 ]. As regards to C and E antigens, frequencies are higher than in our study (C 70% and E 26%) [ 5 , 9 , 12 , 17 ]. Among RhD negative donors, E antigen is absent.…”
Section: Discussionmentioning
confidence: 99%
“…The CCDEE phenotype was rare but more frequently observed (n = 4, table 2) than was predicted by our calculations of the CDE haplotype (n = 0, table 3); the 4 donors were unrelated based on the donors' residence, name, religion, location, and date of blood donation (data not shown). The prevalence of Kell antigens varied markedly among Indian populations: Thakral et al [4] reported for Northern India a K prevalence of 5.68%, which almost resembles the European situation, for instance 7.82% in Germany [11]; in West Bengal the K prevalence was 0.79% (table 1), more typical for most non-Caucasian populations [5].…”
Section: Discussionmentioning
confidence: 99%
“…The common antigens of the Rhesus and Kell blood group systems are also frequently tested in blood donors and patients because of their clinical relevance. Several studies from the 1960s addressed ABO and Rh antigens in various West Bengal populations [1], and several current studies [2][3][4][5][6], conducted in other parts of India, documented the antigen prevalence for the 3 blood group systems. The available data using current technology is limited for the Bengali population in eastern India [7,8] although approximately 91 million people live in the state of West Bengal, bordering Bangladesh to the west and north.…”
Section: Introductionmentioning
confidence: 99%